RANCANG BANGUN APLIKASI ADMINISTRASI PELAYANAN KEPENDUDUKAN PADA PEMERINTAH DESA GUNUNG SARI KABUPATEN BOGOR - Ricki Sastra; Numan musyaffa; Arfhan Prasetyo (NUANSA INFORMATIKA, 2023)
Population information is the most important factor that concerns village government. The development of a village, of course, will be accompanied by an increasing population of residents living in the village, and as the number of residents increases, it will cause difficulty in the process of collecting population data, accessing information, and also making letters needed by residents. Gunung Sari Village in its population administration services requires a system in the form of a website to make it easier for the community to take care of various population files and access information about the village.The information system for population service administration in Gunung Sari Village which until now has not been computerized. The existing system in Gunung Sari Village is still done manually, starting from residents who have to come directly to the village office to take care of their needs and sometimes residents have to go back and forth if the files do not meet the predetermined requirements to take care of their various population files, as well as the dissemination and storage of various data or information still using paper, thus allowing the risk of damage to loss of population data.  The design of this information system is the best solution to solve the problems that exist in this agency, and with a computerized system, an effective and efficient activity can be achieved in supporting activities in this government agency. Keywords: Information System Design, Mail creation system